TiO2 nanotube arrays grafted with Fe2O3 hollow nanorods as integrated electrodes for lithium-ion batteries - Yu, Le (2013)
Novel nano-heterostructures composed of Fe2O3 hollow nanorods on both the outer and inner surface of the aligned TiO2 nanotube arrays (TNAs) have been fabricated by growing FeOOH nanospindles onto the TNAs, and then followed by thermal transformation in air. Owing to their structural advantages, such a hierarchical architecture exhibits superior electrochemical performance with a remarkable areal capacity of over 600 μA h cm−2 at a current density of 100 μA cm−2 for 50 cycles (680 μA h cm−2 at 100 μA cm−2). This hierarchal structure might be easily integrated as a binder-free electrode for microscale lithium-ion batteries considering the improved performance and the simple synthesis.